2020
DOI: 10.1371/journal.pone.0244182
|View full text |Cite
|
Sign up to set email alerts
|

Self-criticism and self-esteem in early adolescence: Do they predict depression?

Abstract: Beck’s theory suggests that forming negative self-cognitions is a key early step in the development of depression. However, others have suggested the reverse, arguing that depression leads to development of negative self-beliefs. As such, there is debate about whether these cognitions are precursors to, or alternatively are caused by, depression. Although Beck’s theory is supported in older adolescents, it has not been clearly seen in younger adolescents. This study aimed to assess the relation between two maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 55 publications
1
25
0
3
Order By: Relevance
“…In addition, SE students obtained significantly lower self-esteem scores than PE students. Research such as that conducted by Gittins and Hunt [78] found that self-esteem levels begin to drop from the age of 12. This occurs due to the emergence of self-criticism and self-evaluations of self-worth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SE students obtained significantly lower self-esteem scores than PE students. Research such as that conducted by Gittins and Hunt [78] found that self-esteem levels begin to drop from the age of 12. This occurs due to the emergence of self-criticism and self-evaluations of self-worth.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the multivariate analysis did not confirm the effect of age on self-esteem. In agreement with this age trend, a study among Australian adolescents showed that their self-esteem was decreasing with age (Gittins and Hunt,) (24) .…”
Section: Concerningmentioning
confidence: 56%
“…No solo eso, sino que también se confirmó que las mujeres sentían las emociones negativas más intensamente que los hombres, por el mismo factor explicado anteriormente [30,45]. La última prevalencia en mujeres (vs. Hombres) en cuanto a las escalas fue la autocrítica, ya que las mujeres son más propensas ser duras y críticas consigo mismas y sus acciones [46]. La única variable que mostró mayores puntuaciones en hombres que en mujeres fue la retirada social, siendo ellos los más propensos a evitar la confrontación del conflicto como indica la literatura científica [13].…”
Section: Discussionunclassified